2022
DOI: 10.3390/life13010060
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Crocus sativus L. Petals Extracts against Foodborne Pathogenic and Spoilage Microorganisms, with a Special Focus on Clostridia

Abstract: In recent years, there has been a growing interest in the use of novel antimicrobial agents able to inhibit or kill food-borne bacteria or to interrupt the onset of food spoilage. Crocus sativus L. petals, typically considered as waste obtained from saffron spice production, could be a source of natural bioactive compounds to be used as food preservatives. The purpose of this work was to investigate the antibacterial properties of two hydroalcoholicsaffron petal extracts obtained by maceration (SPEA) and by ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The in vitro anti-Clostridial effect of different phenolic compounds has already been reported in the literature. A previous study by Primavilla et al [35] refers to the similar antibacterial activity of Crocus sativus L. extract (1 g/mL) assessed by agar well diffusion, albeit C. botulinum and C. perfringens seemed more sensitive than C. difficile. This diverse outcome is of no surprise as the different chemical composition and formulation of the extracts can lead to different results of microbial growth modulation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The in vitro anti-Clostridial effect of different phenolic compounds has already been reported in the literature. A previous study by Primavilla et al [35] refers to the similar antibacterial activity of Crocus sativus L. extract (1 g/mL) assessed by agar well diffusion, albeit C. botulinum and C. perfringens seemed more sensitive than C. difficile. This diverse outcome is of no surprise as the different chemical composition and formulation of the extracts can lead to different results of microbial growth modulation.…”
Section: Discussionmentioning
confidence: 95%
“…Concerning the time-kill test, in a previous study testing saffron natural extracts on the same bacterial strains, the LOQ was reached at around 24 h, reflecting different antibacterial actions most certainly due to the different chemical compositions of the extracts [35]. Manuka (Leptospermum scoparium) honey was reported as having in vitro bactericidal activity and a therapeutic role in the prevention of C. difficile infection [43], in addition to potent biofilm inhibition activity in vitro [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that phytochemicals have great antimicrobial potential with several mechanisms of action against both susceptible and resistant microorganisms [148]. Similarly, it is evident from earlier research that C. sativus petals possess strong antibacterial, antifungal, and antioxidant activity [149,150]. A notable antibacterial activity of saffron petals' methanolic extract was reported by Asgarpanaha et al [151] against Escherichia coli, Bacillus cereus, Salmonella typhi, Staphylococcus aureus, and Shigella dysenteriae.…”
Section: Antimicrobial Activities Of Saffronmentioning
confidence: 92%
“…They have been associated with numerous pharmacological effects [ 22 ]. The results of previous studies have suggested that different parts of Crocus sativus L. can be used for their antioxidant activity [ 23 , 24 ] and antibacterial effects against specific bacteria [ 12 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%